Trazas fósiles como herramienta para reconocer las variaciones de oxigenación: un caso de estudio en la Formación Los Molles (Toarciano - Calloviano inferior) - Campetella, Débora Mical (2020)
The Toarcian - lower Callovian Los Molles Formation in the Chacay Melehue section (southern limb of Cordillera del Viento - Neuquén Basin) comprises offshore-shelf deposits and subordinately, channel-levee and lobe deposits produced by density currents. These deposits are characterized by two distinctive trace fossil suites: (1) Chondrites and Trichichnus in the offshore-shelf mud, and (2) Chondrites, Trichichnus, and Phycosiphon occurring in distal levee deposits. The generally low diversity and abundance of the trace fossils suggest severe environmental conditions. In particular, in the intervals containing Chondrites and Trichichnus, pyrite framboids are abundant and most likely indicate low oxygen availability within the sediment. The presence of Phycosiphon in the levee deposits implies short periods of improved oxygenation caused by the density currents originating in shallow water.